Pentingnya Penerapan Kode Etik Atas Etika Profesi Hukum Pada Profesi Notaris - Astri Dewi Setyarini; Kayus Kayowuan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
A notary is a professional in the legal field who plays an important role in creating legal certainty and assisting the public in various civil legal matters. On this occasion, the author discusses how important the role of the professional code of ethics is for Notaries and how violations are sanctioned for Notaries. By using a normative juridical research method where the author uses studies from existing legal sources, the researcher found that in implementing the code of ethics for Notaries it is very important to maintain public trust in the profession and the sanctions that will be imposed on a Notary who violates it can be in the form of demands or revocation of rights and dismissal in a respectful or dishonorable manner.